Association of antibodies to Plasmodium falciparum reticulocyte binding protein homolog 5 with protection from clinical malaria - Chiu, Chris Y. H.; Healer, Julie; Thompson, Jennifer K.; Chen, Lin; Kaul, Aiki; Savergave, Laxman; Raghuwanshi, Arjun; Li Wai Suen, Connie S. N.; Siba, Peter M.; Schofield, Louis; Mueller, Ivo; Cowman, Alan F.; et al. (Frontiers in Microbiology, 2014)
Emerging evidence suggests that antibodies against merozoite proteins involved in Plasmodium falciparum invasion into the red blood cell (RBC) play an important role in clinical immunity to malaria. The protein family of parasite antigens known as P. falciparum reticulocyte binding protein-like homolog (PfRh) is required for RBC invasion. PfRh5 is the only member within the PfRh family that cannot be genetically deleted, suggesting it plays an essential role in parasite survival. This antigen forms a complex with the cysteine-rich P. falciparum Rh5 interacting protein (PfRipr), on the merozoite surface during RBC invasion. The PfRh5 ectodomain sequence and a C-terminal fragment of PfRipr were cloned and expressed in Escherichia coli and baculovirus-infected cells, respectively. Immunization of rabbits with these recombinant proteins induced antibodies able to inhibit growth of various P. falciparum strains. Antibody responses to these proteins were investigated in a treatment–re-infection study conducted in an endemic area of Papua New Guinea (PNG) to determine their contribution to naturally acquired immunity. Antibody titers to PfRh5 but not PfRipr showed strong association with protection against P. falciparum clinical episodes. When associations with time-to-first infection were analyzed, high antibody levels against PfRh5 were also found to be associated with protection from high-density infections but not from re-infection. Together these results indicate that PfRh5 is an important target of protective immunity and constitutes a promising vaccine candidate.